Identifying hepatic genes regulating the ovine response to gastrointestinal nematodes using RNA-Sequencing - Dixon, Samantha; Karrow, Niel A.; Borkowski, Emma; Suarez-Vega, Aroa; Menzies, Paula I.; Kennedy, Delma; Peregrine, Andrew S.; Mallard, Bonnie A.; Cánovas, Ángela (Frontiers in Genetics, 2023)
Gastrointestinal nematode (GIN) infections are considered the most important disease of grazing sheep and due to increasing anthelmintic resistance, chemical control alone is inadequate. Resistance to GIN infection is a heritable trait, and through natural selection many sheep breeds have higher resistance. Studying the transcriptome from GIN-exposed and GIN-unexposed sheep using RNA-Sequencing technology can provide measurements of transcript levels associated with the host response to GIN infection, and these transcripts may harbor genetic markers that can be used in selective breeding programs to enhance disease resistance. The objective of this study was to compare liver transcriptomes of sheep naturally exposed to GINs, with either high or low parasite burdens, to GIN-unexposed control sheep in order to identify key regulator genes and biological processes associated with GIN infection. Differential gene expression analysis revealed no significant differentially expressed genes (DEG) between sheep with a high or low parasite burden (P-value ≤ 0.01; False Discovery Rate (FDR) ≤ 0.05; and Fold-Change (FC) of > 2). However, when compared to the control group, low parasite burden sheep showed 146 DEG (64 upregulated and 82 downregulated in the low parasite burden group relative to the control), and high parasite burden sheep showed 159 DEG (57 upregulated and 102 downregulated in the low parasite burden group relative to the control) (P-value ≤ 0.01; FDR ≤ 0.05; and FC of > 2). Among these two lists of significant DEG, 86 DEG (34 upregulated, 52 downregulated in the parasited group relative to the control) were found in common between the two parasite burden groups compared to the control (GIN-unexposed sheep). Functional analysis of these significant 86 DEG found upregulated genes involved in immune response and downregulated genes involved in lipid metabolism. Results of this study offer insight into the liver transcriptome during natural GIN exposure that helps provide a better understanding of the key regulator genes involved in GIN infection in sheep.